Support for Regulatory Assessment of Percutaneous Absorption of Retronecine-type Pyrrolizidine Alkaloids through Human Skin - Plaza, Alberto; Toner, Frank; Harris, James; Ottersbach, Peter; Roper, Clive; Mahony, Catherine (Planta Medica, 2021)
1,2-unsaturated pyrrolizidine alkaloids are found naturally in Symphytum officinale, well known as comfrey, which has a longstanding use for the topical treatment of painful muscle and joint complaints. Pyrrolizidine alkaloids (PA) are a relevant concern for the safety assessment due to their liver genotoxicity profile, and close attention is paid during manufacturing to minimizing their levels. Current regulatory risk assessment approaches include setting limits that derive from toxicity data coming from the oral route of exposure. This study investigated to what extent pyrrolizidine alkaloids are bioavailable following topical exposure, assessing penetration of retronecine-type PAs in an in vitro human skin model. A single comfrey root formulation was spiked with 3 different congeners (a 7R-monoester, an open-chained 7R-diester, and a cyclic diester) and percutaneous absorption measured per OECD guidelines and good laboratory practices. The measured penetration for all 3 PAs was low and compared favourably with existing in vitro data. Although consideration of different regulatory guidance influences the determination of dermally absorbed dose, these data facilitate the understanding of absorption differences following topical exposure, which in turn can be taken into account in the risk assessment.
Keywords: Boraginaceae; Symphytum officinale; comfrey root; pyrrolizidine alkaloids; skin penetration; risk assessment